Contribution of radiation therapy of head and neck paragangliomas: About 6 cases presentation - Ghammad, Sanae; Fadwa, Allouche; Fatima Zahra, Terrab; Ghita, Chebihi Hassani; Zenab, Alami; Thouria, Bouhafa; Khalid, Hassouni (Journal of Surgery and Medicine, 2019)
The neck’s paraganglions are bilateral nodular structures, with the same embryological origin which is the cephalic neural crest. They have a branchiomeric distribution. They have an important secreting function during the embryonic life, and then regress when the adrenal medulla starts functioning. Then only carotid and aortic paraganglions have chemoreceptor, baroreceptor and endocrine proved functions. The paragangliomas are tumors developed at the expense of paraganglions by proliferations of the chief cells (of type I) most of the time. Generally these tumors exhibit a slow growth rate, most often presenting asymptomatically as a space occupying mass lesion witnessed clinically or radiographically. The secreting tumors are very rare (5%). The benignity is the rule but the localization near noble structures makes it a highly risky tumor. This disease is often monofocal but it may also be part of a multifocal disease (6%). Advances in imaging have facilitated the diagnosis and the assessment of this disease. Diagnosis is generally made through a combination of clinical findings and radiographic studies. Surgery is the treatment of choice through total subadventitial resection, and rebuilding of the carotid axis when necessary. Surgery may lead to significant morbidity, resulting from major cranial nerve injury and especially at a late stage in the evolution of the disease. The preoperative embolization can facilitate ablation and reduce morbidity. Precisely, external radiotherapy can de indicated for recurrences, tumoral operating residues, and counter indications.